The Loss of a Close Person – Intersections Between Law and Psychology. Case of Polish Law - Drapalska-Grochowicz, Marlena (Medicine, Law & Society, 2023)
The Polish legislator allows for compensation for the harm suffered due to the death of close person resulting from a tort (for example, a car accident). The basis for such claims is Article 446 § 4 of the Polish Civil Code, which contains a vague expression “the closest family member.” Courts must therefore determine whether and how someone was close to someone. The language of the judicial justifications indicates that the courts do not determine proximity solely based on legal criteria. In this publication, I will analyze court decisions in which the scope of the vague expression “the closest family member” has been adjudicated. The analysis aims to establish the legal understanding of closeness in the indicated case and to determine whether and how references to psychology support it.